2006
DOI: 10.2478/s11756-007-0063-y
|View full text |Cite
|
Sign up to set email alerts
|

Structure of chironomid assemblages along environmental and geographical gradients in the Bohemian Forest lakes (Central Europe): An exploratory analysis

Abstract: Eight glacial lakes of the Bohemian Forest (Czech Republic and Germany) were characterised by the distribution of chironomids collected as pupal exuviae. Twenty-eight taxa were identified, including some faunistically interesting species of the region. Two-way indicator species analysis (TWINSPAN) was used to classify lakes according to their taxonomic composition. Canonical correspondence analysis (CCA) and multiple regression were used to relate the chironomid assemblages to two sets of explanatory variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…As analyses of the recent chironomid fauna show (Bitušík & Svitok, 2006), lakes located at lower altitude are inhabited by a more diverse chironomid fauna than lakes at higher elevations (Laka Lake, Prášilské Lake). Although Plešné Lake is among the higher situated lakes, its chironomid species richness is relatively high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As analyses of the recent chironomid fauna show (Bitušík & Svitok, 2006), lakes located at lower altitude are inhabited by a more diverse chironomid fauna than lakes at higher elevations (Laka Lake, Prášilské Lake). Although Plešné Lake is among the higher situated lakes, its chironomid species richness is relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…However, all of these concentrate on changes during shorter periods than are presented in this paper. The first integrated information on the modern chironomid fauna in these lakes of the Bohemian Forest was given by Bitušík & Svitok (2006). The main aim of this paper is to describe the Holocene chironomid stratigraphy of Plešné jezero (Plešné Lake) and to provide a preliminary Holocene reconstruction of key environmental conditions in this area.…”
Section: Introductionmentioning
confidence: 99%
“…A recent investigation based on pupal exuviae analysis (Bitušík & Svitok 2006) showed that differences in taxonomic composition among the Bohemian Forest lakes Brought to you by | MIT Libraries Authenticated Download Date | 5/12/18 6:34 AM could be explained significantly by lake alkalinity (as a proxy of pH). However, chironomids have so far not reflected the effects of acidification in the investigated lakes in such a dramatic way as mayflies and stoneflies (Vrba et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…6), Sialis lutaria was reported from CN and GA already by Frič & Vávra (1897) and Klapálek (1903), respectively. Also, Bitušík & Svitok (2006) analysed recent Chironomid assemblages of all Bohemian Forest lakes from this survey that have suggested different grouping of the lakes.…”
Section: Discussionmentioning
confidence: 99%